Polydatin-curcumin formulation alleviates CTD-ILD-like lung injury in mice via GABBR/PI3K/AKT/TGF-β pathway - Zhang, Zhengju; Zhang, Yao; Lu, Qingyi; Wang, Yanan; Li, Guodong; Jin, Guoju; Ma, Weiguo; Liu, Yuyue; Yang, Lei; Liu, Hui; Zhang, Honghong; Gu, Wen; et al. (Frontiers in Pharmacology, 2025)
Connective tissue disease-associated interstitial lung disease (CTD-ILD) is a systemic autoimmune disease with high morbidity and hazard, characterized by progressive pulmonary inflammation and fibrosis. The monomer formulation of polydatin and curcumin (PD + Cur) for lung injury in CTD-ILD was optimized from Curcumae Longae Rhizoma (Curcuma Longa L.) and Polygoni Cuspidati Rhizoma Et Radix (Polygonum cuspidatum Sieb. et Zucc.). Mice with CTD-ILD-like lung injury were established by a single intratracheal drip of bleomycin. After intervening in model mice for 4 weeks, PD + Cur attenuated alveolar atrophy, fibrillar collagen formation, and thickened alveolar septa in the lung, improved serum biomarkers TOLLIP, MUC5B, KL-6, SP-D, and RCN3, and suppressed serum immunoinflammatory factors IL-6, CCL-18, and SF. The transcriptome sequencing showed that PD + Cur ameliorated CTD-ILD mainly by regulating aberrant immunoinflammation, which was further confirmed by proteomics that the PI3K/AKT/TGF-β pathway was a key pathway. Further, PD + Cur was found to affect amino acid metabolism in the serum significantly. The B-type receptor for GABA (GABBR) agonist baclofen was further found to attenuate CTD-ILD-like lung injury and modulate PI3K/AKT/TGF-β signaling. However, the inhibition of AKT, transforming growth factor beta receptor type 3 (TGFβR3), a key indicator downstream of PI3-kinase subunit p85-alpha (PI3KR1), by PD + Cur was reversed after intervention with the GABBR receptor inhibitor CGP52432. PD + Cur has an ameliorative effect on CTD-ILD-like lung injury by targeting GABBR to modulate the PI3K/AKT/TGF-β pathway.